Characterization of a Haematococcus pluvialis Diacylglycerol Acyltransferase 1 and Its Potential in Unsaturated Fatty Acid-Rich Triacylglycerol Production - Cui, Hongli; Xu, Wenxin; Zhu, Xiaoli; Zhao, Chunchao; Cui, Yulin; Ji, Chunli; Zhang, Chunhui; Xue, Jinai; Qin, Song; Jia, Xiaoyun; Li, Runzhi (Frontiers in Plant Science, 2021)
The unicellular green alga Haematococcus pluvialis has been recognized as an industry strain to produce simultaneously esterified astaxanthin (EAST) and triacylglycerol (TAG) under stress induction. It is necessary to identify the key enzymes involving in synergistic accumulation of EAST and TAG in H. pluvialis. In this study, a novel diacylglycerol acyltransferase 1 was systematically characterized by in vivo and in silico assays. The upregulated expression of HpDGAT1 gene was positively associated with the significant increase of TAG and EAST contents under stress conditions. Functional complementation by overexpressing HpDGAT1 in a TAG-deficient yeast strain H1246 revealed that HpDGAT1 could restore TAG biosynthesis, and exhibited a high substrate preference for monounsaturated fatty acyl-CoAs (MUFAs) and polyunsaturated fatty acyl-CoAs (PUFAs). Notably, heterogenous expression of HpDGAT1 in Chlamydomonas reinhardtii and Arabidopsis thaliana resulted in a significant enhancement of total oils and concurrently a high accumulation of MUFAs- and PUFAs-rich TAGs. Furthermore, molecular docking analysis indicated that HpDGAT1 contained AST binding sites. These findings evidence a possible dual function role for HpDGAT1 involving in TAG and EAST synthesis, demonstrating that it is a potential target gene to enrich AST accumulation in this alga, and to design oil production in both commercial algae and oil crops.